International and Foreign Trends Regulating the Freedom of Artistic Expression - Cseporán, Zsolt (Pécs journal of international and European law, 2017)
Since the middle of the second decade of the 21st century, it can be observed that the concept of the role of the state in the cultural sphere is changing again, especially in light of the growing demands by individuals as consumers of culture. The constitutional regulation of art reflects the current directions, the formulated aims and the professed values of cultural policy. This implies that the legal regulation of culture and arts shows different models at the international and national levels as well.